Specific cancer-associated mutations in the switch III region of Ras increase tumorigenicity by nanocluster augmentation - Maja Šolman; Alessio Ligabue; Olga Blaževitš; Alok Jaiswal; Yong Zhou; Hong Liang; Benoit Lectez; Kari Kopra; Camilo Guzmán; Harri Härmä; John F Hancock; Tero Aittokallio; et al. (United States, 2022)
Hotspot mutations of Ras drive cell transformation and tumorigenesis. Less frequent mutations in Ras are poorly characterized for their oncogenic potential. Yet insight into their mechanism of action may point to novel opportunities to target Ras. Here, we show that several cancer-associated mutations in the switch III region moderately increase Ras activity in all isoforms. Mutants are biochemically inconspicuous, while their clustering into nanoscale signaling complexes on the plasma membrane, termed nanocluster, is augmented. Nanoclustering dictates downstream effector recruitment, MAPK-activity, and tumorigenic cell proliferation. Our results describe an unprecedented mechanism of signaling protein activation in cancer.